Femtosecond Laser-Assisted Intra-Corneal Drug Delivery. (2nd November 2015) - Pallikaris, Ioannis G.; Kymionis, George D.; Plaka, Argyro D.; Binder, Perry S.; Kontadakis, Georgios A.; Tsoulnaras, Konstantinos I.
Abstract: Purpose : To present a case of fungal keratitis that was successfully treated with direct intrastromal medication delivery through a corneal incision created with the femtosecond laser. Methods : A 71-year-old female patient with recurrent episodes of an unresponsive, deep stromal keratitis for six months' duration, resistant to various therapeutic approaches, was referred to our institute. The 150 kHz Intralase iFS laser (Abbott Medical Optics Inc., Santa Ana, CA) was used to create a corneal pocket in an attempt to permit drug delivery directly into the corneal abscess. Results : Five days after the intrastromal injections, the clinical condition was improved. Two years after the procedure, the cornea is stable and free of any clinical signs or symptoms of recurrence. Conclusions : In this case report, an alternative application of femtosecond laser technology is presented, performing intrastromal drug delivery through a corneal incision for the treatment of fungal keratitis.